An Analysis of Roland Barthes' Semiotic Theory: Focusing on Denotation, Connotation, and Myth - Barus, Efendi; Aisyah, Aisyah; Siregar, Elvi Fauziah; Risnawaty, Risnawaty (PT Inovasi Pratama Internasional, 2025)
This article has an objective to discuss Roland Barthes’ semiotic theory. It focuses on the concepts of denotative meaning, connotative meaning and mythological meaning and builds upon Ferdinand de Saussure’s foundational semiotics. This research has a common methodological way of writing that is by using qualitative method or library research. The result of discussion is applicable to Barthes’ theory in comprehending of sign ways to account for cultural and ideological dimensions. His model of myth as a second order of semiological systems offers a powerful frame work for comprehending the ways in which everyday objects and media carry deeper ideological meanings. Through the analysis of selected texts of media, this research postulates how denotation and connotation are exemplified and providing literal and non-literal meanings. Denotative meaning provides literal meaning, connotation gives interpretative depth or individual meaning, as myth naturalizes ideological construction and it becomes part of artificial meanings. This article makes the conclusion that Barthes’ theory of semiotics is essential for critically decoding message in contemporary media culture.